Multilayer imaging and compositional analysis of human male breast by laser reflectometry and Monte Carlo simulation - Pandian, P. S; Kumaravel, M; Singh, Megha (Medical & biological engineering & computing, 2009)
The laser backscattering from biological tissues depends on their composition and blood flow. The onset of abnormalities in tissues is associated with the change in composition at a specific location which may affect laser backscattering. The objective of this work is to study the point-to-point compositional variation of male breast tissues as this site has been prone to cancer development. The normalized backscattered intensity (NBI) profiles at various locations of human chest region of five subjects by multi-probe laser reflectometer are obtained. Based on these data the images of tissue composition, showing the point-to-point changes at various depths from the tissue surface, are reconstructed. The analysis of data shows that the maximum NBI variation is at the pectoralis major muscle and minimum variation is observed at the sternum. The optical parameters, based on the NBI data obtained for five human subjects, show the maximum increase in absorption (p < 0.0001) and minimum change in scattering (p < 0.0001) coefficients compared to that as observed at the sternum. Also the minimum absorption and maximum scattering coefficients are observed at the pectoralis major muscles. The regional variations of NBI and optical parameters further support these findings. The variations in the NBI and optical parameters may indicate the compositional change in tissues, which could be used for diagnostic and therapeutic applications of laser.